Activation of Shc1 Allows Oncostatin M to Induce RANKL and Osteoclast Formation More Effectively Than Leukemia Inhibitory Factor - Persson, Emma; Souza, Pedro P. C.; Floriano-Marcelino, Thais; Conaway, Howard Herschel; Henning, Petra; Lerner, Ulf H. (Frontiers in Immunology, 2019)
Background and Purpose: The gp130 family of cytokines signals through receptors dimerizing with the gp130 subunit. Downstream signaling typically activates STAT3 but also SHP2/Ras/MAPK pathways. Oncostatin M (OSM) is a unique cytokine in this family since the receptor (OSMR) activates a non-redundant signaling pathway by recruitment of the adapter Shc1. We have studied the functional relevance of Shc1 for OSM-induced bone resorption. Experimental Approach: Osteoblasts were stimulated with OSM and STAT3 and Shc1 activations were studied using real-time PCR and Western blots. The role of STAT3 and Shc1 for OSM-induced RANKL expression and osteoclast formation was studied by silencing their mRNA expressions. Effects of OSM were compared to those of the closely related cytokine leukemia inhibitory factor (LIF). Key Results: OSM, but not LIF, induced the mRNA and protein expression of Shc1 and activated phosphorylation of Shc1 in the osteoblasts. Silencing of Shc1 decreased OSM-induced activation of STAT3 and RANKL expression. Silencing of STAT3 had no effect on activation of Shc1, but prevented the OSM-mediated increase of RANKL expression. Silencing of either Shc1 or STAT3 in osteoblasts decreased formation of osteoclasts in OSM-stimulated co-cultures of osteoblasts and macrophages. In agreement with these observations, OSM was a more potent and robust stimulator than LIF of RANKL formation and bone resorption in mouse calvariae and osteoclast formation in bone marrow cultures. Conclusions and Implications: Activation of the Shc1-dependent STAT3 signaling is crucial for OSM-induced osteoclast formation. Inhibition of Shc1 is a potential mechanism to specifically inhibit OSM-induced bone resorption.